2008
DOI: 10.5194/acp-8-7055-2008
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: The CCCma third generation AGCM and its extension into the middle atmosphere

Abstract: Abstract. The Canadian Centre for Climate Modelling and Analysis third generation atmospheric general circulation model (AGCM3) is described. The discussion summarizes the details of the complete physics package emphasizing the changes made relative to the second generation version of the model. AGCM3 is the underlying model for applications which include the IPCC fourth assessment, coupled atmosphere-ocean seasonal forecasting, the first generation of the CCCma earth system model (CanESM1), and middleatmosphe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
186
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(196 citation statements)
references
References 76 publications
5
186
0
Order By: Relevance
“…The fourth version of the Canadian RCM (Caya andLaprise 1999, de Elía andCôté 2010) used in this study was driven by the third generation of the CGCM3 (Scinocca et al 2008) being developed by the Canadian Center for Climatic Modeling and Analysis (CCCma). The CGCM3 has four main components: a general atmospheric circulation model (with 31 vertical levels), a general ocean circulation model, an ice-sea thermodynamic model and a soilvegetation model.…”
Section: Canadian Regional Climate Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth version of the Canadian RCM (Caya andLaprise 1999, de Elía andCôté 2010) used in this study was driven by the third generation of the CGCM3 (Scinocca et al 2008) being developed by the Canadian Center for Climatic Modeling and Analysis (CCCma). The CGCM3 has four main components: a general atmospheric circulation model (with 31 vertical levels), a general ocean circulation model, an ice-sea thermodynamic model and a soilvegetation model.…”
Section: Canadian Regional Climate Modelmentioning
confidence: 99%
“…The A2 emissions scenario used in this study is one of the scenarios that follows most closely recent observed emissions trends (Raupach et al 2007). The five climate projections selected are driven by five different members of the Canadian coupled global climate model (CGCM3) (Scinocca et al 2008) and provide a range of plausible future climate differentiated by natural variability (the five members of CGCM3 differ only in their initial conditions). RCMs, such as CRCM4, are especially well adapted to climatic conditions such as those found in the study area, which is located along the coast and is subject to local valley effects.…”
Section: Introductionmentioning
confidence: 99%
“…simulations with different initial conditions, of these simulations are used. In addition, one CLM simulation uses realisation four of the CCCma3 (Scinocca et al 2008) at a T47 horizontal resolution. For both GCMs the responses to the IPCC SRES A1B forcing scenario are investigated in comparison to the twentieth century anthropogenic forcing only simulations.…”
Section: Gcmsmentioning
confidence: 99%
“…Herein we use output from three RCMs: regional climate model 3 (RegCM3) (22), Canadian regional climate model (CRCM) (23), and third generation Hadley Centre regional climate model (HRM3) (24). The three AOGCMs used to provide the lateral boundary conditions are Geophysical Fluid Dynamics Laboratory model (GFDL) (CM2.1) (25), Canadian model version 3 (CGCM3) (26), and Hadley Centre model, third generation (HadCM3) (27). Further, a set of numerical experiments in which the RCMs are nested within output from the NCEP-DoE global reanalysis (17) are analyzed to investigate differences in wind energy density during the historical period that derive from using AOGCM output rather than observations (as approximated in the reanalysis dataset).…”
mentioning
confidence: 99%